Correlation between Interleukin-6 with D-dimer and C-reactive protein Levels in Patients with Confirmed COVID-19 Severe Criteria - Gemintang, Ghea Setia; Wiratmoko, Raden Mirsyam Ratri; Tubarad, Gladys Dwiani Tinovella (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: In Coronavirus Disease 2019 (COVID-19) severe criteria, cytokine storm conditions are often found, and there will be an increase in Interleukin-6 as a cytokine and CRP as an acute phase protein induced by IL-6. In COVID-19 patients with severe criteria, coagulation disorders can also be found, characterized by an increase in the D-dimer value. Purpose: To determine the correlation between IL-6, D-dimer, and CRP levels in patients with confirmed COVID-19 severe criteria at Bunda Margonda General Hospital in 2021. Methods: This research was an analytical observation study with a cross-sectional approach, using secondary data from medical records of patients with confirmed COVID-19 severe criteria at Bunda Margonda General Hospital in 2021. Results: The number of patients with confirmed COVID-19 severe criteria was primarily male (59%), aged 46-55 years (33%), with degree of severity with severe criteria in 100 patients, increased IL-6 (91%), increased D-dimer levels (90%), increased CRP levels (95%). There was a correlation between increased IL-6 with D-dimer levels (p-value 0,005) and a correlation between increased IL-6 with CRP levels (p-value of 0,000). A simultaneous and significant relationship was found between IL-6, D-dimer, and CRP levels in severe COVID-19 criteria. COVID-19 patients with severe criteria were more commonly found in males in the 46-55-year age group with increased IL-6, D-dimer, and CRP values. Conclusion: There was a correlation between increased IL-6 and D-dimer and CRP levels in COVID-19 patients with severe criteria at Bunda Margonda General Hospital in 2021.